Insulin resistance and development of diabetes mellitus associated with megestrol acetate therapy. Issue 848 (June 1996) - Jain, P.; Girardi, L. S.; Sherman, L.; Berelowicz, M.; Smith, L. G.
Abstract : We describe a case of diabetes mellitus induced by megestrol acetate in a patient with the acquired immunodeficiency syndrome. Metabolic studies including an arginine infusion test excluded an insulinopenic state and suggested insulin resistance as the underlying mechanism for hyperglycaemia. Withdrawal of megestrol acetate resulted in rapid correction of all metabolic abnormalities and eliminated the need for exogenous insulin therapy.